Motives to practice physical education and sport and its impact on the development of motor skills concerning pupils at secondary school level. A practical study in secondary schools of Reggane town - RABAH, ABD ENNASSER; HARITI, HAKIM (sports creativity, 2025)
the purpose of this research aim to know the relation that exist between motives and its link to motor movement to pupils while practicing physical education and sports at the secondary school level which is affected by many action that develop the motor skills and to compare between literary pupils motives and scientific ones the school and between the integrated skills. This is a complementary and a continued chon of activities shown thorough true motor behavior in sports situations and perfect practice in motor control , en order to reach the purpose of the research the researcher user a method to study the relation that links between the different changes thus the survey is done on 200 pupils (boys and girls)aged between 16 and 19 , we put a practical means on them whish are : physical and fitness motives and tendencies of sports ,metal motives , sport success motives , external encouragement motives . the results suggest that there are differences statically significant between the learners of the two streams in motives and the development of motor skills